Barriers and facilitators to lifestyle behavior change and goal setting in adolescents with polycystic ovary syndrome - Gadiraju, Manasa; Kim, Joy Y.; Green, Erin M.; MacMillan Uribe, Alexandra; Chang, Honghui; Burgert, Tania S.; Olfert, Melissa D.; Vanden Brink, Heidi (Frontiers in Nutrition, 2025)
PurposeTo identify barriers and facilitators to lifestyle modifications and goal setting and characterize goal setting for adolescents with polycystic ovary syndrome (PCOS).MethodsRetrospective chart review of registered dietitian nutritionist (RDN) nutrition notes from 118 adolescents with PCOS 11–21 years evaluated at a multi-specialty PCOS clinic. Goals, barriers, and facilitators were coded using open coding and a priori objectives and characterized for emerging themes using qualitative content analysis.ResultsFive major themes of barriers and facilitators to behavior change emerged: interest and motivation, family involvement, resources and food environment, taste preferences, and self-efficacy. RDNs set ≥3 goals with 52%, 2 goals with 35%, 1 goal with 9%, and no goals with 3% of adolescents with PCOS. Goals covered three major themes: incorporation of the United States Department of Agriculture (USDA) MyPlate model, modifying carbohydrate intake, and increasing physical activity.ConclusionThe facilitators and barriers identified through our analysis are both similar and different to those reported in adolescents with obesity and women with PCOS, likely due to differences in condition specific contexts and life stage. The goals recorded by RDNs reflect a desire to increase diet quality; however, too many goals may have been set on average. Overall, adolescents with PCOS report intrapersonal, interpersonal, and environmental barriers and facilitators that may affect their ability to establish and act upon goals.